Combination of Medium-High-Hydrostatic-Pressure Treatment with Post-/Pre-Heat Treatment for Pasteurization of Bacillus subtilis Spore Suspended in Soy Milk - Morimatsu Kazuya (Microorganisms, 2025)
Medium-high-hydrostatic-pressure (MHHP) treatment can induce the spore to germinate via activating the germination receptor, subsequently resulting in the loss of the heat resistance of the spore and finally killing the germinated spore, although the ungerminated spore, even after MHHP treatment, can survive. This study aims to clarify the pasteurization effect of the combination of MHHP treatment with post-/pre-heating treatment on Bacillus subtilis spores suspended in soy milk as a food model. Regarding the results, the D value, as a known heat resistance indicator of the MHHP-treated spore, decreased in comparison with the untreated spore. However, the activation energies required for killing both the untreated and the MHHP-treated spores were equivalent, which indicated that the heat conductivity of the ungerminated spores might be increased by MHHP treatment. When the spore was subjected to pre-heating treatment and subsequently to MHHP treatment, the pasteurization effect of MHHP treatment differed with the pre-heating temperature. Pre-heating treatment at 80 °C could promote pasteurization, while that at 90–100 °C could suppress it, which might be caused by the heat activation/inactivation of germination receptors. From these results, the presence of post-/pre-heat treatment could be an important factor for the pasteurization of B. subtilis spores via MHHP treatment.